Antibacterial Activity of Costuspictus Extracts Against Bacillus subtilis, Escherichia coli, Pseudomonasand Staphylococcus by Cup Diffusion Method (International Journal of Food and Nutritional Sciences, 2023)
Costuspictus, also known as insulin plant, is a medicinal herb commonly used in traditional medicine for its potential to help manage blood sugar levels. The present study aims to investigate the antibacterial potential of different concentrations ofCostuspictusextracts viz.,25%, 50%, 75% and 100%using different solvents viz.,Ethanol, methanol, petroleum ether, acetone and water against four prominent bacterial strains viz.,Bacillus subtilis, Escherichia coli,Pseudomonas and Staphylococcus.Ampicillin was used as standard. The extraction was carried out using the dry plant sample for 5hrs in five different solvents with increasing polarity. The extracts, in each solvent except water were obtained by using a soxhlet extractor. The water extract was obtained by using 50 g of the dry plant sample and mixing well in a blender. The extracts were then evaporated to dryness. The dry powder thus obtained was tested for antibacterial activity. 1mg of the dry sampleextract was resuspended in 1ml of the respective solvent and used as stock. The cup diffusion method was employed to assess Minimum Inhibitory Concentration and area of inhibitionon the growth of these bacteria. The study provides valuable insights into the potential application of Costuspictus as a natural antibacterial agent.